Factors associated with poor adherence to vaccination against hepatitis viruses, streptococcus pneumoniae and seasonal influenza in HIV-infected adults. Issue 2 (1st February 2019) - Tsachouridou, Olga; Georgiou, Adamantini; Naoum, Symeon; Vasdeki, Dimitra; Papagianni, Maria; Kotoreni, Georgia; Forozidou, Evropi; Tsoukra, Paraskevi; Gogou, Christiana; Chatzidimitriou, Dimitrios; Skoura, Lemonia; Zebekakis, Pantelis; et al.
ABSTRACT: Introduction : Vaccination against various pathogens is recommended for HIV positive adults. There are not sufficient data either on vaccination coverage of HIV positive adults or the risk factors associated with poor adherence to routine vaccination. Patients-Methods : During the period 2004–2014 vaccination coverage of a group of HIV infected adults against hepatitis A virus (HAV), hepatitis B virus (HBV), seasonal influenza virus and pneumococcal disease was recorded. Vaccination coverage was separated into two chronological periods, before and after 2010, as 2010 marks the start of the economic crisis in Greece. Results : 1210 patients were included in our study. Vaccine coverage throughout the study for hepatitis B, hepatitis A, seasonal influenza and pneumococcal infection was 73.6%, 70.4%, 39% and 79%, respectively. The complete lack of insurance coverage was an independent factor of non-compliance in all proposed vaccines (vaccination against pneumococcal disease: OR: 0.82 95%CI: 0.49–1.35, vaccination against HBV: OR: 0.82, 95% CI: 0.45–1.49, vaccination against HAV OR: 0.54, 95%CI: 0.34–0.87, vaccination against influenza: OR: 1.27, 95% CI: 0.76–2.10). In addition, low educational level was associated with poor compliance to vaccination against pneumococcal disease, hepatitis A, hepatitis B, and influenza. Finally, the recommendation for vaccination after the onset of the economic crisis (2010) led to poor compliance to vaccination against HBV, HAV and pneumococcal disease, but not against influenza. Conclusions : In our study, vaccination coverage for vaccine-preventable diseases was found to be insufficient for HIV positive adults in Northern Greece. Also, low educational level, lack of insurance coverage and economic distress have contributed to poor vaccine compliance, leading to poor protection of the HIV positive population and decreased immune coverage in the community.